2017
DOI: 10.1189/jlb.5ru0817-315r
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia relapse after CD19-targeted chimeric antigen receptor T cell therapy

Abstract: CART19 therapy has revolutionized the treatment of CD19 acute lymphoblastic leukemia, demonstrating an unprecedented complete remission rate; however, as follow-up prolongs, a high relapse rate after CART19 therapy has emerged as one of the major problems. Relapse can be attributed to the loss of leukemic cell immunogenicity, diminished function and amount of CART19 cells, and the inhibitory bone marrow microenvironment. Although studies to prevent and treat relapse have begun, some encouraging results have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…However, studies have shown that glucocorticoid treatment of CRS may reduce the efficacy of CAR-T treatment, which is a controversial finding that needs further elucidation [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that glucocorticoid treatment of CRS may reduce the efficacy of CAR-T treatment, which is a controversial finding that needs further elucidation [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical trials showed anti‐CD19 CAR‐T therapy attained high remission rates, and caused relatively controllable adverse events in r/r B‐ALL patients . Nonetheless, due to the antigen escape of tumor cells, impaired function and reduced amount of CAR‐T cells, and the inhibitory microenvironment of bone marrow, patients who have achieved complete remission (CR) through CAR‐T therapy are still at high risk of relapse …”
Section: Introductionmentioning
confidence: 99%
“…Up to date, frequencies and subsequences of CD19 positive and CD19 dim or negative relapse are still unclear. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%